EVALUATION OF SALIVARY ENZYMES IN POST MENOPAUSAL WOMEN WITH AND WITHOUT PERIODONTITIS - B., Santhosh Shenoy; Shenoy, Prajnya; Talwar, Avaneendra; Thomas, Biju; Sharath, K.S.; K., Shamila Shetty (Journal of Health and Allied Sciences NU, 2014)
Aim: To compare the levels of Lactate dehydrogenase (LDH) and alkaline phosphatase (ALP) in post-menopausal women with and without periodontitisMethodology: A cross-sectional pilot study was conducted. A total of 50 postmenopausal women were recruited and categorized into two groups based on their periodontal status. Their salivary samples were collected and subjected to Lactate dehydrogenase (LDH) and alkaline phosphatase (ALP) estimation in the laboratoryResults: The activity of LDH and ALP were significantly higher in the post-menopausal women with periodontitis than those without periodontitis.Conclusion: The present study demonstrated post-menopausal women may have exaggerated inflammatory response to dental plaque.
Keywords: Lactate dehydrogenase (LDH); Alkaline phosphatase (ALP); post-menopause; periodontitis; saliva